WHY THE ARAB LEARNERS OF ENGLISH LANGUAGE COMMITT ERRORS IN PRONUNCIATION AND GRAMMAR : A PSYCHOLINGUISTIC APPROACH TO THE STUDY - AWAJ, ESSAM; MOHAMED, MOHAMMED (مجلة العلوم الإنسانية والتطبيقية, 2017)
This paper makes a psycholinguistic approach to observe and analyze why the Arab learners of English language commit errors in pronunciation and grammar. It also presents the suggestions. First, it phonologically analyzes the English phonotactics in the English of Arab learners of English as a foreign language to determine the types of pronunciation difficulties they encounter. More specifically, it investigates the types of declusterization processes found in their interlingual communication and the sources of such processes. The results of this study demonstrate that Arab learners of English unintentionally insert an anapestic vowel in the onset as well as in the coda of certain English syllables. Results also show that the major reason for declusterization processes is the mother tongue influence. In order to overcome such difficulties, this paper suggests a new approach for teaching and learning English language syllable structure system. Secondly, it focuses on the errors committed in grammar by analyzing it psycholinguistically.